Ramadan fasting and exercise combination therapy: A novel approach for osteoporosis prevention in ovariectomized rats - Albrahim, Tarfa; Alangry, Raghad; Alotaibi, Raghad; Almandil, Leen; Alburikan, Sara; Aloudah, Hisham S.; Alahmed, Mohammed; Alonazi, Mona (Frontiers in Physiology, 2024)
Background: Osteoporosis is a chronic bone metabolic disease that affects millions of people worldwide, particularly the elderly and postmenopausal women. It is characterized by weakened bones, increasing the risk of fractures and leading to significant morbidity and mortality. The goal of the current study is to examine whether the reported osteo-preservative effects of exercise and/or fasting in the Ramadan fasting model (RFM) in ovariectomized (OVX) rats. Methods:The experimental intervention started one month following the ovariectomy procedure and consisted of five 15-minute exercise sessions per week at 18-25 m/min and/or an approximately 13-hour fast from sunrise to sunset (6:00 AM -19:00 PM). Serum bone metabolism biomarker levels were measured, and mineral concentrations in femoral ashed bones and digested serum were determined. Additionally, serum bone alkaline phosphatase (b-ALP), parathyroid hormone, osteocalcin, calcitonin, and vitamin D3 concentrations were measured using the competitive enzyme immunoassay technique. Results: Calcium, magnesium, and phosphorus showed a notable decrease in mineral concentration among OVX rat femurs compared with the combination group (OVX+RFM+E) and control groups. In addition, homeostasis of serum concentrations of calcium, magnesium, and phosphorus were observed increase in the OVX+RFM+E group rather than the OVX group without intervention when compared with a control group. Furthermore, fasting and exercise, either alone or concurrently with ovariectomy, induced a non-significant elevation in osteocalcin, parathyroid hormone, and vitamin D3 whereas b-ALP and calcitonin increased significantly compared with control rats. Conclusion:The combination of the Ramadan fasting model and moderate intensity exercises among OVX rats manifested advantageous effects in bone biomarkers compared with OVX rats without intervention. This could be recommended as a lifestyle modification protective against osteoporosis, especially in the context of depleted estrogen hormone in post-menopause.